Common mental disorders among men in countryside of São Paulo – SP (Research, Society and Development, 2022)
Objective: to investigate aspects related to social determinants of health and its possible relationship with CMD. Methods: observational, sectional epidemiological research. The sample consisted of 370 men, living in the countryside of São Paulo. A structured questionnaire with open and closed questions was used, containing a short version of the Self Reporting Questionnaire. For data analysis, the SPSS® 21 software was used. The study was approved by the Ethics and Research Committee of the Hospital at Universidade Federal Fluminense. Results: the global prevalence of suspicion for common mental disorders found was 20%. After applying a binary multiple logistic regression model, they maintained an association for the outcome: drug addiction; smoking; carrying out integrative practices; perception of bad sleep. Conclusion: vulnerabilities were observed, such as low education, unemployment and low income. There was little search for health prevention and self-care habits, physical inactivity, irregular eating habits and search for health services for emergencies.